2011
DOI: 10.1103/physrevb.84.214405
|View full text |Cite
|
Sign up to set email alerts
|

Spin and orbital ordering in Y1xLaxVO3

Abstract: The spin and orbital ordering in Y 1-x La x VO 3 (0.30 ≤ x ≤ 1.0) has been studied to map out the phase diagram over the whole doping range 0 ≤ x ≤ 1. The phase diagram is compared with that for RVO 3 (R = rare earth or Y) perovskites without A-site variance.For x > 0.20, no long-range orbital ordering was observed above the magnetic ordering temperature T N ; the magnetic order is accompanied by a lattice anomaly at a T t ≤ T N as in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 18 publications
3
26
0
Order By: Relevance
“…Above 200 K, no evidence for orbital ordering has been observed, suggesting that the orbitals are fluctuating. This is corroborated by thermal conductivity measurements and Raman scattering experiments [6,25,26] that show unambiguously that the orbitals are fluctuating above T OO while some degree of orbital fluctuation is retained in the interval between T N < T < T OO . Complete static orbital order is only achieved below T CG .…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…Above 200 K, no evidence for orbital ordering has been observed, suggesting that the orbitals are fluctuating. This is corroborated by thermal conductivity measurements and Raman scattering experiments [6,25,26] that show unambiguously that the orbitals are fluctuating above T OO while some degree of orbital fluctuation is retained in the interval between T N < T < T OO . Complete static orbital order is only achieved below T CG .…”
Section: Introductionsupporting
confidence: 61%
“…When YVO 3 is doped with La 3+ as in Y 1−x La x VO 3 , it was previously shown that the T OO transition is quickly suppressed and disappears by x = 0.2 [6]. Coupled with this suppression is the disappearance of the transition to the monoclinic phase as well, in the 77 -200 K range, prior to reentering the orthorhombic phase.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In order to calculate the entropy release across the magnetic transition, we estimated the lattice specific heat with the Thirring model. 27 The calculated entropy change is shown in the inset of Fig. 3.…”
mentioning
confidence: 99%
“…On the contrary, electrons injected in the body of nanotubes (or in the interstices) by DM-electron scatterings, might go through the walls, with definite transmission coefficients, and undergo multi-scattering events, crossing several nanotubes, before exiting from the array. As a benchmark for our analysis, we have used the results of some experimental studies on the determination of transmission coefficients of electrons through graphene planes [12][13][14][15][16]. More information from experiments of this kind would be extremely useful for determining directly also reflection and absorption coefficients.…”
mentioning
confidence: 99%